A Rare Nidus for Biliary Stone Formation: Post-Cholecystectomy Clip Migration - Robert Battat; Marilyse Drapeau; Jonathan Wyse; Bernard Faulques (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
A 54-year-old woman presented with one month of recurrent postprandial right sided and epigastric abdominal pain, associated with intermittent anorexia and vomiting. Her past medical history includes Crohn's disease diagnosed in 1976, requiring total colectomy and end ileostomy in 1977 and small bowel resection for fibrotic stricture in 1980. A cholecystectomy for biliary pancreatitis was performed in 2004.